ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR DUA VARIABEL MENGGUNAKAN PROSEDUR NEWMAN PADA KELAS VIII SMPS KASIH YOBEL SINGKAWANG - Paternus Surya Dino; Ahmad Yani; Bistari (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine student errors in solving story problems of a two-variable linear equation system using the Newman procedure. This type of research is descriptive qualitative research. The subjects in this study involved 6 high school students. The object of this research is the students mistakes in solving the story problems of a two-variable linear equation system. Data collection techniques used are diagnostic test questions and directv communication (interviews). This study concludes that students still make mistakes based on theh Newman procedure. There are five stages of errors in the Newman procedure in solving mathematical problems, namely: (1) errors in rewriting that known in the problem and being unable to interpret the meaning of words, (2) being unable to understand the questions and questions referred to in the problem, (3) unable to change the story problem into a mathematical model according to the procedure and do not know the formula that used, (4) unable to solve the problem using arithmetic operations correctly and incorrectly results in the calculation operation, (5) unable to complete the final result and cannot conclude accordingly with what is asked in the question. The causes of these problems are lack of understanding of the questions, unable to capture problem information contained in the questions, lack of practice in working on the form of story questions, mistaking information from the teacher.